/ ANALYSIS OF THE FINANCIAL BALANCE SHEET OF THE REPUBLIC OF SERBIA IN THE PERIOD FROM 2010-2018.: / - Bakić, Sanja (Poslovna ekonomija, 2020)
The balance of payments of one country represents the realization of transactions between two countries. The subject of the research is the analysis of the period from 2010 to 2018 and the presentation of the impact of positions of goods, services, primary income and personal transfers on the current account of the balance of payments, as well as covering current position positions through capital. The aim of the research in this paper is to examine the importance of opening the borders of the Republic of Serbia and enabling the entry of foreign investors. The expected results of the research should indicate the way to reduce the current account deficit, the balance of payments itself, as well as the economic development and stability of the country.